Composition, method for producing substrate, and polymer

A composition with specific polymers and solvents forms high-density films on substrates with metal atoms, addressing the challenges of selective modification and easy removal, enhancing semiconductor device processing.

JP7622639B2Active Publication Date: 2025-01-28JSR CORPORATION
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021556121
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-12
Filing Date
2020-11-11
Publication Date
2025-01-28
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

Conventional methods struggle to form fine patterns on semiconductor devices due to optical limitations and fail to achieve selective surface modification and easy removal of chemical modifications on substrates without damaging the base material.

Method used

A composition containing specific polymers with functional groups and solvents is used to form a high-density film on substrates with metal atoms, allowing selective modification and easy removal through wet peeling, enhancing blocking performance for metal oxide formation.

Benefits of technology

The method enables selective and high-density film formation on substrates with metal atoms, demonstrating excellent blocking performance for metal oxide formation, suitable for future semiconductor device processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622639000011
    Figure 0007622639000011
  • Figure 0007622639000012
    Figure 0007622639000012
  • Figure 0007622639000001
    Figure 0007622639000001
Patent Text Reader

Abstract

Provided are: a composition by which a wet-peelable film can be region-selectively formed with a high density on a surface of a substrate containing metal atoms at the surface thereof, said film being capable of exhibiting high ability to block formation of a metal oxide through ALD or CVD; a production method for the substrate; and a polymer. A composition comprising: a polymer having at least one first group selected from the group consisting of groups including two or more cyano groups, groups including -B(OR)2, groups including -PO(OR)2, and groups including -P(OR)2 (where R each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1-10 carbon atoms); and a solvent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to compositions, methods for making substrates, and polymers. [Background technology]

[0002] As semiconductor devices continue to shrink, there is a demand for technology to form fine patterns of less than 30 nm, but conventional lithography methods are becoming technically difficult due to optical factors and other factors.

[0003] Therefore, the formation of fine patterns using so-called bottom-up techniques has been considered. As the bottom-up techniques, in addition to a method utilizing self-organization of polymers, a method of selectively modifying a substrate having a fine region on the surface layer has been considered. This selective modification method requires a material that can modify the surface region easily and highly selectively, and various materials have been considered (see JP 2016-25355 A, JP 2003-76036 A, ACS Nano, 9, 9, 8710, 2015, ACS Nano, 9, 9, 8651, 2015, Science, 318, 426, 2007, and Langmuir, 21, 8234, 2005). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-25355 A [Patent Document 2] JP 2003-76036 A [Non-patent literature]

[0005] [Non-Patent Document 1] ACS Nano,9,9,8710,2015 [Non-Patent Document 2] ACS Nano,9,9,8651,2015 [Non-Patent Document 3] Science, 318, 426, 2007 [Non-Patent Document 4] Langmuir,21,8234,2005 Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, patterns have been deposited on the surface of a substrate by forming metal oxides using the ALD (Atomic Layer Deposition) method or the CVD (Chemical Vapor Deposition) method, and it is required that this pattern deposition be performed with high selectivity by distinguishing regions. On the other hand, it is also required that the chemical modification performed on the surface of the substrate can be easily removed by wet peeling while reducing the influence on the substrate. However, the above-mentioned conventional materials cannot meet these requirements.

[0007] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a composition, a method for producing a substrate, and a polymer that can form a region-selective, wet-peelable film at a high density on the surface of a substrate containing metal atoms in a surface layer, and that can exhibit high blocking performance against metal oxide formation by an ALD method or a CVD method using this film. [Means for solving the problem]

[0008] The invention made to solve the above problems is a composition containing a polymer having at least one first group (hereinafter also referred to as "group (X)") selected from the group consisting of a group containing two or more cyano groups, a group containing -B(OR)2, a group containing -PO(OR)2, and a group containing -P(OR)2 (wherein R is each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms) (hereinafter also referred to as "polymer [A]") and a solvent (hereinafter also referred to as "solvent [B]").

[0009] Another invention made to solve the above-mentioned problems is a method for manufacturing a substrate, comprising the steps of applying the composition directly or indirectly to a substrate (hereinafter also referred to as "substrate (S)") containing metal atoms (hereinafter also referred to as "metal atoms (M)") in a surface layer, and heating the coating film formed by the application step.

[0010] Still another invention made to solve the above problems is a polymer having at least one group selected from the group consisting of a group containing two or more cyano groups, a group containing -B(OR)2, a group containing -PO(OR)2, and a group containing -P(OR)2, at an end of the main chain or an end of the side chain (wherein each R is independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms). Effect of the Invention

[0011] According to the composition and the method for producing a substrate of the present invention, a film capable of being wet-peeled in a selective area can be formed at a high density on the surface of a substrate containing metal atoms in the surface layer, and this film can exhibit high blocking performance against metal oxide formation by the ALD method or the CVD method. The polymer of the present invention can be suitably used as a polymer component of the composition. Therefore, the composition, the method for producing a substrate, and the polymer can be suitably used in the processing of semiconductor devices, which are expected to become increasingly finer in the future. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram illustrating region-selective chemical modification of the surface of a substrate containing metal atoms in the surface layer with the composition of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating the blocking performance of metal oxide formation by the ALD method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Composition> The composition contains a polymer [A] and a solvent [B]. The composition may contain any optional components as long as the optional components do not impair the effects of the present invention.

[0014] The composition contains a polymer [A] and a solvent [B]. The polymer [A] has a group (X), so that a film capable of being wet-peeled in a selective area can be formed at a high density on the surface of a substrate containing metal atoms in the surface layer, and this film can exhibit high blocking performance against metal oxide formation by the ALD method or CVD method. The reason why the composition has the above-mentioned configuration and exhibits the above-mentioned effect is not necessarily clear, but it can be inferred, for example, as follows. That is, the polymer [A] has a group (X) that bonds with a metal atom (M), so that a film that chemically modifies a region selectively can be formed on the surface of a substrate (S) containing a metal atom (M) in the surface layer, as shown in FIG. 1, and this film is considered to be wet-peeled using an acid-containing liquid or the like. Furthermore, as shown in FIG. 2, it is considered that the use of such a film can improve blocking performance against metal oxide formation by the ALD method or CVD method.

[0015] Each component contained in the composition will be described below.

[0016] <[A] Polymer> The polymer [A] is a polymer having a group (X). Examples of the structural units constituting the polymer [A] include a structural unit derived from substituted or unsubstituted styrene, a structural unit derived from (meth)acrylic acid or a (meth)acrylic acid ester, a structural unit derived from substituted or unsubstituted ethylene, and a structural unit containing a crosslinkable group. The polymer [A] may have one or more of these structural units. The "crosslinkable group" refers to a group that forms a crosslinked structure by a reaction under heating conditions, active energy ray irradiation conditions, acidic conditions, or the like.

[0017] Examples of monomers that provide structural units derived from substituted or unsubstituted styrene include styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, pt-butylstyrene, 2,4,6-trimethylstyrene, p-methoxystyrene, pt-butoxystyrene, o-vinylstyrene, m-vinylstyrene, p-vinylstyrene, o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, m-chloromethylstyrene, p-chloromethylstyrene, p-chlorostyrene, p-bromostyrene, p-iodostyrene, p-nitrostyrene, and p-cyanostyrene.

[0018] Examples of monomers that provide structural units derived from (meth)acrylic acid esters include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylic acid cycloalkyl esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 1-methylcyclopentyl (meth)acrylate, 2-ethyladamantyl (meth)acrylate, and 2-(adamantan-1-yl)propyl (meth)acrylate; (Meth)acrylic acid aryl esters such as phenyl (meth)acrylate and naphthyl (meth)acrylate; Examples of the substituted alkyl (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 3-hydroxyadamantyl (meth)acrylate, 3-glycidylpropyl (meth)acrylate, and 3-trimethylsilylpropyl (meth)acrylate.

[0019] Examples of monomers which provide structural units derived from substituted or unsubstituted ethylene include ethylene; Alkenes such as propene, butene, and pentene; Vinylcycloalkanes such as vinylcyclopentane and vinylcyclohexane; Cycloalkenes such as cyclopentene and cyclohexene; Examples thereof include 4-hydroxy-1-butene, vinyl glycidyl ether, and vinyl trimethylsilyl ether.

[0020] Examples of the crosslinkable group include Groups containing a polymerizable carbon-carbon double bond, such as a vinyl group, a vinyloxy group, an allyl group, a (meth)acryloyl group, or a styryl group; cyclic ether groups such as an oxiranyl group, an oxiranyloxy group, an oxetanyl group, or an oxetanyloxy group; an aryl group fused with a cyclobutane ring, such as a phenyl group fused with a cyclobutane ring, or a naphthyl group fused with a cyclobutane ring; an aryl group having an aromatic hydroxy group protected by an acyl group such as an acetoxyphenyl group or a t-butoxyphenyl group, or a thermally dissociable group; An aryl group bound to an acyl group such as an acetoxymethylphenyl group or a methoxymethylphenyl group, or a methylol group (-CHOH) protected by a thermally dissociable group; Examples of the sulfanylmethylphenyl group include aryl groups having a substituted or unsubstituted sulfanylmethyl group (-CH2SH) bonded thereto, such as a sulfanylmethylphenyl group and a methylsulfanylmethylphenyl group.

[0021] The aryl groups condensed with a cyclobutane ring form a covalent bond under heating conditions.

[0022] "Acyl group" refers to a group obtained by removing OH from a carboxylic acid, which replaces and protects the hydrogen atom of an aromatic hydroxy group or a methylol group. "Thermally dissociable group" refers to a group that replaces the hydrogen atom of an aromatic hydroxy group, a methylol group, or a sulfanylmethyl group, and dissociates upon heating.

[0023] Examples of the acyl group in an aryl group to which a protected aromatic hydroxy group, methylol group or sulfanylmethyl group is bonded include a formyl group, an acetyl group, a propionyl group, a butyryl group and a benzoyl group.

[0024] Examples of the thermally dissociable group in the aryl group having a protected aromatic hydroxy group bonded thereto include tertiary alkyl groups such as t-butyl and t-amyl groups, etc. Examples of the thermally dissociable group in the aryl group having a protected methylol or sulfanylmethyl group bonded thereto include alkyl groups such as methyl, ethyl and propyl groups, etc.

[0025] Examples of the structural unit containing a crosslinkable group include a structural unit derived from a vinyl compound having a crosslinkable group, and a structural unit derived from a (meth)acrylic compound having a crosslinkable group.

[0026] [Group(X)] The group (X) is at least one selected from the group consisting of a group containing two or more cyano groups, a group containing -B(OR)2, a group containing -PO(OR)2, and a group containing -P(OR)2 (wherein R is each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms). The group (X) has a plurality of polar groups, which further improves substrate selectivity, and as a result, a film can be formed that chemically modifies regions selectively on the surface of the base material (S) containing metal atoms (M) in the surface layer.

[0027] The group (X) bonds to the metal atom (M). This bond is, for example, a chemical bond, such as a covalent bond, an ionic bond, or a coordinate bond. Among these, a coordinate bond is preferred from the viewpoint of a stronger bond between the metal atom (M) and the group (X).

[0028] Examples of the group containing two or more cyano groups include a group containing -CH=C(CN)2 and a group containing -CH(CN)2.

[0029] Examples of the group containing -CH=C(CN)2 include *-CH=C(CN)2 and *-R'-CH=C(CN)2. R' is an alkanediyl group having 1 to 20 carbon atoms. * indicates a bonding site with the polymer [A].

[0030] Examples of the group containing -CH(CN)2 include *-CH(CN)2 and *-R'-CH(CN)2. R' is an alkanediyl group having 1 to 20 carbon atoms. * indicates a bonding site with the polymer [A].

[0031] Examples of the group containing -B(OH)2 include *-B(OH)2 and *-R'-B(OH)2. R is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. R' is an alkanediyl group having 1 to 20 carbon atoms. * indicates a bonding site with the polymer [A].

[0032] Examples of the group containing -PO(OR)2 include *-PO(OR)2 and *-R'-PO(OR)2. R is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. R' is an alkanediyl group having 1 to 20 carbon atoms. * indicates a bonding site with the polymer [A].

[0033] Examples of the group containing -P(OR)2 include *-P(OR)2 and *-R'-P(OR)2. R is a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. R' is an alkanediyl group having 1 to 20 carbon atoms. * indicates a bonding site with the polymer [A].

[0034] The term "hydrocarbon group" includes linear hydrocarbon groups, alicyclic hydrocarbon groups, and aromatic hydrocarbon groups. This "hydrocarbon group" may be a saturated or unsaturated hydrocarbon group. The term "linear hydrocarbon group" refers to a hydrocarbon group that does not include a cyclic structure and is composed only of a linear structure, and includes both linear and branched hydrocarbon groups. The term "alicyclic hydrocarbon group" refers to a hydrocarbon group that includes only an alicyclic structure as a ring structure and does not include an aromatic ring structure, and includes both monocyclic alicyclic hydrocarbon groups and polycyclic alicyclic hydrocarbon groups. However, it is not necessary for the group to be composed only of an alicyclic structure, and it may include a linear structure as a part of the ring structure. The term "aromatic hydrocarbon group" refers to a hydrocarbon group that includes an aromatic ring structure as a ring structure. However, it is not necessary for the group to be composed only of an aromatic ring structure, and it may include a linear structure or an alicyclic structure as a part of the ring structure.

[0035] Examples of the monovalent hydrocarbon group having 1 to 10 carbon atoms represented by R include a monovalent chain hydrocarbon group having 1 to 10 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 10 carbon atoms, and a monovalent aromatic hydrocarbon group having 6 to 10 carbon atoms.

[0036] Examples of the monovalent chain hydrocarbon group having 1 to 10 carbon atoms include Alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, and a tert-butyl group; alkenyl groups such as ethenyl, propenyl, and butenyl; Examples of the alkynyl group include an ethynyl group, a propynyl group, and a butynyl group.

[0037] Examples of the monovalent alicyclic hydrocarbon group having 3 to 10 carbon atoms include alicyclic saturated hydrocarbon groups such as a cyclopentyl group, a cyclohexyl group, a norbornyl group, and an adamantyl group; Examples of the alkyl group include alicyclic unsaturated hydrocarbon groups such as a cyclopentenyl group, a cyclohexenyl group, and a norbornenyl group.

[0038] Examples of the monovalent aromatic hydrocarbon group having 6 to 10 carbon atoms include Aryl groups such as a phenyl group, a tolyl group, a xylyl group, and a naphthyl group; Examples of the alkyl group include aralkyl groups such as a benzyl group and a phenethyl group.

[0039] R is preferably a hydrogen atom, a chain hydrocarbon group, or an aromatic hydrocarbon group, more preferably a hydrogen atom or a chain hydrocarbon group, further preferably a hydrogen atom or an alkyl group, and particularly preferably a hydrogen atom.

[0040] Among these, as the group (X), from the viewpoint of achieving higher regioselectivity of the chemical modification, a group containing two or more cyano groups, a group containing -B(OR)2, or a group containing -PO(OR)2 is preferred, and a group containing two or more cyano groups, a group containing -B(OH)2, or a group containing -PO(OH)2 is more preferred.

[0041] The polymer [A] preferably has the group (X) at the end of the main chain or at the end of the side chain. The "main chain" refers to the longest atomic chain among the atomic chains constituting the polymer [A]. The "side chain" refers to the atomic chain other than the main chain among the atomic chains constituting the polymer [A].

[0042] The group (X) at the end of the main chain can be introduced, for example, by treating the polymerization end of living anionic polymerization with a terminal treatment agent that provides the group (X).

[0043] Examples of the terminal treatment agent which gives the group (X) include N,N-dimethylformamide, diisopropyl bromoethyl borate, diethyl chlorophosphate and the like.

[0044] A group containing two or more cyano groups can be formed, for example, by reacting a group formed using N,N-dimethylformamide with malononitrile. A group containing -B(OH)2 can be formed, for example, using diisopropyl bromomethyl borate. A group containing -PO(OH)2 can be formed, for example, by hydrolysis of a group formed using diethyl chlorophosphate in a solvent such as propylene glycol monomethyl ether in the presence of a base such as triethylamine.

[0045] The polymer [A] having a group (X) at the end of its side chain can be formed, for example, by using as a monomer a monomer having a group (X) at the end and an ethylenic carbon-carbon double bond.

[0046] In order to improve the region selectivity of chemical modification, the polymer [A] preferably has the group (X) at an end of the main chain, and more preferably has the group (X) at one end of the main chain.

[0047] The lower limit of the weight average molecular weight (Mw) of the polymer [A] in terms of polystyrene standards, as determined by gel permeation chromatography (GPC), is preferably 1,000, more preferably 2,000, even more preferably 4,000, and particularly preferably 4,500. The upper limit of the Mw is preferably 50,000, more preferably 30,000, even more preferably 15,000, and particularly preferably 8,000.

[0048] The upper limit of the ratio of the number average molecular weight (Mn) of the polymer [A] converted into polystyrene by GPC to Mw (Mw / Mn, dispersity) is preferably 5, more preferably 2, more preferably 1.5, and particularly preferably 1.3. The lower limit of the ratio is usually 1, and preferably 1.05.

[0049] The Mw and Mn of the polymer in this specification are values ​​measured by gel permeation chromatography using GPC columns (two "G2000HXL", one "G3000HXL" and one "G4000HXL") manufactured by Tosoh Corporation under the following conditions. Eluent: Tetrahydrofuran (FUJIFILM Wako Pure Chemical Industries, Ltd.) Flow rate: 1.0mL / min Sample concentration: 1.0% by mass Sample injection volume: 100 μL Column temperature: 40℃ Detector: Differential refractometer Standard material: Monodisperse polystyrene

[0050] The lower limit of the content of the polymer [A] is preferably 80 mass %, more preferably 90 mass %, and even more preferably 95 mass %, based on all components other than the solvent [B] in the composition. The upper limit of the content is, for example, 100 mass %.

[0051] <[B] Solvent> The solvent (B) is not particularly limited as long as it is a solvent that can dissolve or disperse at least the polymer (A) and other components.

[0052] Examples of the solvent (B) include alcohol-based solvents, ether-based solvents, ketone-based solvents, amide-based solvents, ester-based solvents, and hydrocarbon-based solvents.

[0053] Examples of alcohol-based solvents include Aliphatic monoalcohol solvents having 1 to 18 carbon atoms, such as 4-methyl-2-pentanol and n-hexanol; Alicyclic monoalcohol solvents having 3 to 18 carbon atoms, such as cyclohexanol; Polyhydric alcohol solvents having 2 to 18 carbon atoms, such as 1,2-propylene glycol; Examples of the solvent include partial ether solvents of polyhydric alcohols having 3 to 19 carbon atoms, such as propylene glycol monomethyl ether.

[0054] Examples of ether solvents include dialkyl ether solvents such as diethyl ether, dipropyl ether, dibutyl ether, dipentyl ether, diisoamyl ether, dihexyl ether, and diheptyl ether; Cyclic ether solvents such as tetrahydrofuran and tetrahydropyran; Examples of the solvent include aromatic ring-containing ether solvents such as diphenyl ether and anisole (methyl phenyl ether).

[0055] Examples of ketone solvents include Chain ketone solvents such as acetone, methyl ethyl ketone, methyl-n-propyl ketone, methyl-n-butyl ketone, diethyl ketone, methyl-iso-butyl ketone (MIBK), 2-heptanone (methyl-n-pentyl ketone), ethyl-n-butyl ketone, methyl-n-hexyl ketone, di-iso-butyl ketone, and trimethylnonanone; Cyclic ketone solvents such as cyclopentanone, cyclohexanone, cycloheptanone, cyclooctanone, and methylcyclohexanone; Examples include 2,4-pentanedione, acetonylacetone, and acetophenone.

[0056] Examples of amide solvents include Cyclic amide solvents such as N,N'-dimethylimidazolidinone and N-methylpyrrolidone; Examples of the solvent include chain amide solvents such as N-methylformamide, N,N-dimethylformamide, N,N-diethylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, and N-methylpropionamide.

[0057] Examples of ester solvents include Monocarboxylic acid ester solvents such as n-butyl acetate and ethyl lactate; Polyhydric alcohol carboxylate solvents such as propylene glycol acetate; Polyhydric alcohol partial ether carboxylate solvents such as propylene glycol monomethyl ether acetate; Lactone solvents such as γ-butyrolactone and δ-valerolactone; Polycarboxylic acid diester solvents such as diethyl oxalate; Examples of the carbonate solvent include dimethyl carbonate, diethyl carbonate, ethylene carbonate, and propylene carbonate.

[0058] Examples of the hydrocarbon solvent include Aliphatic hydrocarbon solvents having 5 to 12 carbon atoms, such as n-pentane and n-hexane; Examples of the solvent include aromatic hydrocarbon solvents having 6 to 16 carbon atoms, such as toluene and xylene.

[0059] Among these, ester-based solvents are preferred, polyhydric alcohol partial ether carboxylate-based solvents are more preferred, and propylene glycol monomethyl ether acetate is even more preferred. The composition may contain one or more types of solvent [B].

[0060] <Optional ingredients> The composition may contain, as optional components, an acid generator, a surfactant, and the like.

[0061] [Acid generator] The acid generator is a compound that generates an acid when heated or irradiated with active energy rays. Examples of the acid generator include ionic compounds and nonionic compounds.

[0062] Examples of ionic acid generators include triphenylsulfonium, 1-dimethylthionaphthalene, 1-dimethylthio-4-hydroxynaphthalene, 1-dimethylthio-4,7-dihydroxynaphthalene, 4-hydroxyphenyldimethylsulfonium, benzyl-4-hydroxyphenylmethylsulfonium, 2-methylbenzyl-4-hydroxyphenylmethylsulfonium, 2-methylbenzyl-4-acetylphenylmethylsulfonium, 2-methylbenzyl-4-benzoyloxyphenylmethylsulfonium, 1-(4-n-butoxynaphthalene-1-yl)tetrahydrothiophene, and the like. Examples of the salt include salts of cations such as phenyliodonium, 1-(4,7-dibutoxy-1-naphthalenyl)tetrahydrothiophenium, diphenyliodonium, and di(t-butylphenyl)iodonium with anions such as fluorinated alkylsulfonates such as methanesulfonate, trifluoromethanesulfonate, and nonafluorobutanesulfonate, sulfonate ions such as camphorsulfonate and p-toluenesulfonate ions, phosphate ions such as hexafluorophosphate ions, borate ions such as tetrafluoroborate ions, and antimonate ions such as hexafluoroantimonate ions. Among these, salts of triphenylsulfonium cation and fluorinated alkylsulfonate ions are preferred, and triphenylsulfonium nonafluorobutane-1-sulfonate is more preferred.

[0063] Examples of nonionic acid generators include halogen-containing compounds, diazomethane compounds, sulfone compounds, sulfonate compounds, carboxylate compounds, phosphate compounds, N-sulfonyloxyimide compounds, and sulfonebenzotriazole compounds.

[0064] Examples of the N-sulfonyloxyimide compound include N-(trifluoromethylsulfonyloxy)succinimide, N-(2-trifluoromethylphenylsulfonyloxy)phthalimide, and the like.

[0065] When the composition contains an acid generator, the lower limit of the content of the acid generator is preferably 0.1 parts by mass, more preferably 0.5 parts by mass, even more preferably 1 part by mass, and particularly preferably 2 parts by mass, relative to 100 parts by mass of the polymer [A]. The upper limit of the content is preferably 50 parts by mass, more preferably 30 parts by mass, even more preferably 10 parts by mass, and particularly preferably 6 parts by mass.

[0066] [Method of preparing the composition] The composition can be prepared, for example, by mixing the polymer [A], the solvent [B], and any optional components as required in a predetermined ratio, and filtering the mixture through a high-density polyethylene filter having pores of preferably 0.45 μm or less. The lower limit of the solid content concentration of the composition is preferably 0.1% by mass, more preferably 0.5% by mass, and even more preferably 0.7% by mass. The upper limit of the solid content concentration is preferably 30% by mass, more preferably 10% by mass, and even more preferably 3% by mass. The "solid content concentration" refers to the concentration (% by mass) of all components in the composition other than the solvent [B].

[0067] <Substrate manufacturing method> The method for producing the substrate includes a step of directly or indirectly applying a composition to a substrate having a surface layer containing metal atoms (hereinafter also referred to as a "coating step"), and a step of heating the coating film formed by the coating step (hereinafter also referred to as a "heating step"). In the method for producing the substrate, the composition described above is used as the composition.

[0068] According to the method for manufacturing a substrate, the composition described above is used, so that a region-selective wet-peelable film can be formed at high density on the surface of a base material containing metal atoms in its surface layer, and this film can exhibit high blocking performance against metal oxide formation by the ALD method or the CVD method.

[0069] The method for manufacturing the substrate may include, after the heating step, a step of removing the portion of the coating film formed on the region (II) described below, after the heating step, with a rinsing liquid (hereinafter also referred to as the "rinsing step").

[0070] The method for manufacturing a substrate may include, after the rinsing step, a step of depositing a pattern on the surface of the base material (S) after the rinsing step by a CVD method or an ALD method (hereinafter also referred to as a "deposition step").

[0071] The method for manufacturing the substrate may further include a step of contacting the film formed by the heating step with a removing liquid (hereinafter, also referred to as a "removing step") after the heating step, thereby enabling the formed film to be wet peeled off.

[0072] Each step will be described below.

[0073] [Coating process] In this process, the composition is applied directly or indirectly to a substrate (S) containing metal atoms in its surface layer, thereby forming a coating film on the substrate (S) directly or via another layer.

[0074] (base material) The substrate (S) contains metal atoms (M) in a surface layer.

[0075] The metal atom (M) is not particularly limited as long as it is an atom of a metal element. Silicon is a nonmetallic atom and does not fall under the category of a metal atom. Examples of the metal atom (M) include copper, iron, zinc, cobalt, aluminum, tin, tungsten, zirconium, titanium, tantalum, germanium, molybdenum, ruthenium, gold, silver, platinum, palladium, nickel, etc. Among these, copper, cobalt, or tungsten is preferred.

[0076] Examples of the form in which the metal atoms (M) are contained in the surface layer include simple metals, alloys, conductive nitrides, metal oxides, and silicides.

[0077] Examples of the metal element include copper, iron, cobalt, tungsten, tantalum, and the like. Examples of the alloy include a nickel-copper alloy, a cobalt-nickel alloy, and a gold-silver alloy. Examples of conductive nitrides include tantalum nitride, titanium nitride, iron nitride, and aluminum nitride. Examples of metal oxides include tantalum oxide, aluminum oxide, iron oxide, and copper oxide. The silicide may be, for example, iron silicide, molybdenum silicide, or the like. Among these, a metal element, an alloy, a conductive nitride, or a silicide is preferred, a metal element or a conductive nitride is more preferred, copper element, cobalt element, tungsten element, tantalum element, titanium nitride, or tantalum nitride is further preferred, and copper element, cobalt element, or tungsten element is particularly preferred.

[0078] The substrate (S) preferably has a region (hereinafter also referred to as "region (I)") containing metal atoms (M) on the surface layer, and a region (hereinafter also referred to as "region (II)") not containing metal atoms (M) on the surface layer. Region (II) is preferably composed substantially only of nonmetal atoms (hereinafter also referred to as "nonmetal atoms (N)"). When the substrate (S) has both region (I) and region (II), the surface of region (I) containing metal atoms (M) on the surface layer can be selectively chemically modified.

[0079] Examples of the form in which the nonmetallic atom (N) is contained in the region (II) include a nonmetallic element, a nonmetallic oxide, a nonmetallic nitride, and a nonmetallic oxide nitride.

[0080] Examples of the nonmetallic element include elements such as silicon and carbon. An example of the non-metal oxide is silicon oxide. Examples of non-metallic nitrides include SiNx and Si3N4. The non-metal oxide nitride may be, for example, SiON. Of these, non-metal oxides are preferred, and silicon oxide is more preferred.

[0081] The shape of the region (I) and the region (II) in the substrate (S) is not particularly limited, and examples of the shape include a planar shape, a dot shape, a stripe shape, etc. The size of the region (I) and the region (II) is not particularly limited, and the region can be of any desired size.

[0082] The shape of the base material (S) is not particularly limited, and it can be any desired shape such as a plate (substrate) or a sphere.

[0083] The composition can be applied, for example, by spin coating.

[0084] [Heating process] In this step, the coating film formed in the coating step is heated, which promotes the formation of bonds between the metal atoms (M) in the surface layer of the substrate (S) and the groups (X) of the polymer [A] in the composition.

[0085] Examples of the heating means include an oven and a hot plate. The lower limit of the heating temperature is preferably 80°C, more preferably 100°C, and even more preferably 130°C. The upper limit of the heating temperature is preferably 400°C, more preferably 300°C, and even more preferably 200°C. The lower limit of the heating time is preferably 10 seconds, more preferably 1 minute, and even more preferably 2 minutes. The upper limit of the heating time is preferably 120 minutes, more preferably 10 minutes, and even more preferably 5 minutes.

[0086] The average thickness of the film formed can be adjusted to a desired value by appropriately selecting the type and concentration of the polymer [A] in the composition, and the conditions in the heating step, such as the heating temperature and heating time. The lower limit of the average thickness of the film is preferably 0.1 nm, more preferably 1 nm, and even more preferably 3 nm. The upper limit of the average thickness is, for example, 20 nm. The average thickness of the film is a value measured using a spectroscopic ellipsometer (JAWOOLLAM's "M2000D").

[0087] [Rinse process] In this step, the portion of the coating film formed on the region (II) after the heating step is removed with a rinse liquid, whereby the portion of the coating film after the heating step that contains the [A] polymer that is not bonded to the metal atom (M) is removed, and a substrate (S) in which the region (I) is selectively chemically modified is obtained.

[0088] As the rinse liquid, an organic solvent is usually used, for example, a polyhydric alcohol partial ether carboxylate solvent such as propylene glycol monomethyl ether acetate, or a monoalcohol solvent such as isopropanol.

[0089] In this manner, a film having excellent heat resistance can be selectively formed in the region (I) containing metal atoms (M) in the surface layer of the substrate (S). The obtained substrate can be treated, for example, by carrying out the following deposition process.

[0090] [Deposition process] In this step, a pattern is deposited by CVD or ALD on the surface of the substrate (S) after the rinsing step. This allows a metal oxide pattern to be selectively formed in the region (II) that is not chemically modified with the polymer [A]. According to the method for producing the substrate, the composition described above is used to form a film with excellent heat resistance, thereby making it possible to increase the ALD tolerance, and as a result, a metal oxide pattern can be more selectively formed in the region (II).

[0091] [Removal process] In this step, a removal liquid is brought into contact with the film formed by the heating step, whereby the formed film can be easily removed by wet peeling while reducing the influence on the substrate (S).

[0092] The removal liquid is preferably a liquid containing an acid or a liquid containing a base. Examples of the acid include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, and carboxylic acids such as acetic acid, citric acid, oxalic acid, maleic acid, isobutyric acid, and 2-ethylhexanoic acid. Among these, carboxylic acids are preferred, and acetic acid or citric acid is more preferred. Examples of the base include sodium hydroxide, potassium hydroxide, sodium carbonate, sodium silicate, sodium metasilicate, ammonia, ethylamine, n-propylamine, diethylamine, di-n-propylamine, triethylamine, methyldiethylamine, dimethylethanolamine, and triethanolamine. Among these, ammonia or triethylamine is preferred.

[0093] Other examples of the removal liquid include an ammonium hydroxide-hydrogen peroxide aqueous solution (SC-1 cleaning liquid) and a hydrochloric acid-hydrogen peroxide aqueous solution (SC-2 cleaning liquid).

[0094] The solvent of the removal liquid is preferably composed mainly of water. The lower limit of the content of water in the solvent is preferably 50% by mass, more preferably 90% by mass, and even more preferably 99% by mass. The content may be 100% by mass.

[0095] The lower limit of the acid concentration in the acid-containing liquid is preferably 0.1% by mass, more preferably 1% by mass, and even more preferably 3% by mass.The upper limit of the concentration is, for example, 100% by mass, more preferably 90% by mass, and even more preferably 50% by mass.

[0096] <Polymer> The polymer has at least one group selected from the group consisting of a group containing two or more cyano groups, a group containing -B(OR)2, a group containing -PO(OR)2, and a group containing -P(OR)2, at an end of the main chain or an end of the side chain (wherein each R is independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms).

[0097] When the polymer is used as a component of the above-mentioned composition, a film that can be wet-peeled off can be formed selectively in an area on the surface of a substrate that contains metal atoms in the surface layer, and this film can exhibit high blocking performance against metal oxide formation by the ALD method or the CVD method.

[0098] This polymer is described above as polymer [A] in the composition. EXAMPLES

[0099] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various physical properties are shown below.

[0100] [Mw and Mn] The Mw and Mn of the polymer were measured by gel permeation chromatography (GPC) using Tosoh Corporation's GPC columns (two "G2000HXL", one "G3000HXL" and one "G4000HXL") under the following conditions. Eluent: Tetrahydrofuran (FUJIFILM Wako Pure Chemical Industries, Ltd.) Flow rate: 1.0mL / min Sample concentration: 1.0% by mass Sample injection volume: 100 μL Column temperature: 40℃ Detector: Differential refractometer Standard material: Monodisperse polystyrene

[0101] <Synthesis of polymer [A]> [Synthesis Example 1] (Synthesis of Polymer (A-1) (PS-ω-CN)) After drying a 500mL flask reaction vessel under reduced pressure, 120g of tetrahydrofuran (THF) that had been distilled and dehydrated under a nitrogen atmosphere was poured in and cooled to -78°C. Next, 2.38mL of a 1N cyclohexane solution of sec-butyl lithium (sec-BuLi) was poured into this THF, and then 13.3mL of styrene that had been adsorbed and filtered with silica gel and dehydrated by distillation was dripped in over 30 minutes, with care taken not to allow the internal temperature of the reaction solution to rise to -60°C or higher. After stirring for 30 minutes after the dripping was completed, 0.19mL of 3-bromopropionitrile was poured in to perform a termination reaction of the polymerization terminal. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with methyl isobutyl ketone (MIBK). 1,000g of a 2% by mass aqueous solution of oxalic acid was poured into the resulting solution, stirred, and allowed to stand, and the lower aqueous layer was removed. This operation was repeated three times to remove the metal salt. Then, 1,000 g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. This operation was repeated three times to remove the oxalic acid, and the solution was concentrated and dropped into 500 g of methanol to precipitate a polymer, and the solid was collected using a Buchner funnel. This solid was dried under reduced pressure at 60°C to obtain 11.9 g of a white polymer represented by the following formula (A-1) (hereinafter also referred to as "polymer (A-1)" or "PS-ω-CN"). This polymer (A-1) had Mw of 6,000, Mn of 5,600, and Mw / Mn of 1.08.

[0102] [ka]

[0103] [Synthesis Example 2] (Synthesis of Polymer (A-2) (PS-ω-PhBOH)) After drying a 500mL flask reaction vessel under reduced pressure, 120g of THF that had been distilled and dehydrated under a nitrogen atmosphere was poured in and cooled to -78°C. Next, 2.30mL of a 1N cyclohexane solution of sec-BuLi was poured into this THF, and then 13.3mL of styrene that had been adsorbed and filtered with silica gel and dehydrated by distillation was dripped in over 30 minutes, with care taken not to allow the internal temperature of the reaction solution to rise to -60°C or higher. After stirring for 30 minutes after the dripping was completed, 0.72g of 2,4,6-triphenylboroxine and 1mL of methanol were added to perform a termination reaction of the polymerization terminals. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. 1,000g of a 2% by mass aqueous solution of oxalic acid was poured into the resulting solution, stirred, and allowed to stand, after which the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. After repeating this operation three times, the solution was concentrated and dropped into 500 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The solid was dried under reduced pressure at 60°C to obtain 12.1 g of a white polymer represented by the following formula (A-2) (hereinafter also referred to as "polymer (A-2)" or "PS-ω-PhBOH"). This polymer (A-2) had an Mw of 5,600, an Mn of 5,300, and an Mw / Mn of 1.06.

[0104] [ka]

[0105] [Synthesis Example 3] (Synthesis of Polymer (A-3) (PS-ω-(CN)2)) After drying a 500mL flask reaction vessel under reduced pressure, 120g of THF that had been distilled and dehydrated under a nitrogen atmosphere was poured in and cooled to -78°C. Next, 2.38mL of a 1N cyclohexane solution of sec-BuLi was poured into this THF, and then 13.3mL of styrene that had been adsorbed and filtered with silica gel and dehydrated by distillation was dripped in over 30 minutes, taking care not to let the internal temperature of the reaction solution rise above -60°C. After stirring for 30 minutes after the dripping was completed, 0.18mL of N,N-dimethylformamide was poured in to perform a termination reaction of the polymerization terminal. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. 1,000g of a 2% aqueous solution of oxalic acid was poured into the resulting solution, stirred, and allowed to stand, after which the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. After repeating this operation three times, the solution was concentrated and dropped into 500 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The solid was dried under reduced pressure at 60°C to obtain 11.9 g of a white polymer. The polymer had an Mw of 5,000, an Mn of 4,800, and an Mw / Mn of 1.04.

[0106] Next, 10.0 g of this polymer was dissolved in 40 g of toluene, 0.21 g of malononitrile, 0.25 g of ammonium acetate, and 0.038 g of acetic acid were added, and the mixture was heated and dry-distilled under a nitrogen atmosphere for 4 hours. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. 500 g of a 2% aqueous solution of sodium bicarbonate was poured into the resulting solution, stirred, and allowed to stand, after which the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000 g of ultrapure water was poured and stirred to remove the lower aqueous layer. After repeating this operation three times, the solution was concentrated and dropped into 500 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The solid was dried under reduced pressure at 60 ° C. to obtain 9.8 g of a white polymer represented by the following formula (A-3) (hereinafter also referred to as "polymer (A-3)" or "PS-ω-(CN)2"). This polymer (A-3) had an Mw of 5,300, an Mn of 5,100, and an Mw / Mn of 1.04.

[0107] [ka]

[0108] [Synthesis Example 4] (Synthesis of Polymer (A-4) (PS-ω-B(OH)2)) After drying a 500mL flask reaction vessel under reduced pressure, 120g of THF that had been distilled and dehydrated under a nitrogen atmosphere was poured in and cooled to -78°C. Then, 2.30mL of a 1N cyclohexane solution of sec-BuLi was poured into this THF, and then 13.3mL of styrene that had been adsorbed and filtered with silica gel and dehydrated by distillation was dripped in over 30 minutes, taking care not to let the internal temperature of the reaction solution exceed -60°C. After stirring for 30 minutes after the dripping was completed, 0.47mL of diisopropyl bromoethyl borate was poured in to perform a termination reaction of the polymerization terminal. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. 1,000g of a 2% aqueous solution of oxalic acid was poured into the resulting solution, stirred, and allowed to stand, after which the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. After repeating this operation three times, the solution was concentrated and dropped into 500 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The solid was dried under reduced pressure at 60°C to obtain 11.7 g of a white polymer represented by the following formula (A-4) (hereinafter also referred to as "polymer (A-4)" or "PS-ω-B(OH)2"). This polymer (A-4) had Mw of 5,100, Mn of 4,800, and Mw / Mn of 1.04.

[0109] [ka]

[0110] [Synthesis Example 5] (Synthesis of Polymer (A-5) (PS-ω-POEt2)) After drying a 500mL flask reaction vessel under reduced pressure, 120g of THF that had been distilled and dehydrated under a nitrogen atmosphere was poured in and cooled to -78°C. Then, 2.30mL of a 1N cyclohexane solution of sec-BuLi was poured into this THF, and then 13.3mL of styrene that had been adsorbed and filtered with silica gel and dehydrated by distillation was dripped in over 30 minutes, taking care not to let the internal temperature of the reaction solution exceed -60°C. After stirring for 30 minutes after the dripping was completed, 0.33mL of diethyl chlorophosphate was poured in to perform a termination reaction of the polymerization terminal. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. Then, 1,000g of a 2% aqueous solution of oxalic acid was poured in and stirred, and after standing, the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. After repeating this operation three times, the solution was concentrated and dropped into 500 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The solid was dried under reduced pressure at 60°C to obtain 11.5 g of a white polymer represented by the following formula (A-5) (hereinafter also referred to as "polymer (A-5)" or "PS-ω-PO3Et2"). This polymer (A-5) had Mw of 5,100, Mn of 4,900, and Mw / Mn of 1.04.

[0111] [ka]

[0112] [Synthesis Example 6] (Synthesis of Polymer (A-6) (PS-ω-PO3H2)) 0.81g of triethylamine, 4g of propylene glycol monomethyl ether, and 40g of propylene glycol monomethyl ether acetate were added to 10.0g of the polymer (A-5) synthesized in Synthesis Example 5, and the mixture was heated and stirred at 80°C under a nitrogen atmosphere. The reaction solution was heated to room temperature, and the resulting reaction solution was concentrated and replaced with MIBK. Then, 500g of a 2% aqueous solution of oxalic acid was poured in and stirred, and after standing, the lower aqueous layer was removed. This operation was repeated three times. Then, 1,000g of ultrapure water was poured in and stirred, and the lower aqueous layer was removed. After repeating this operation three times, the solution was concentrated and dropped into 500g of methanol to precipitate the polymer, and the solid was collected with a Buchner funnel. The solid was dried under reduced pressure at 60°C to obtain 9.2g of a white polymer represented by the following formula (A-6) (hereinafter also referred to as "polymer (A-6)" or "PS-ω-PO3H2"). This polymer (A-6) had Mw of 5,100, Mn of 4,800, and Mw / Mn of 1.06.

[0113] [ka]

[0114] [Synthesis Example 7] (Synthesis of Polymer (A-7) (PS-ω-CH(CN)2)) 5 g of the polymer (A-3) synthesized in Synthesis Example 3 was dissolved in 40 g of toluene, 0.15 g of sodium borohydride was added, and the mixture was stirred at room temperature for 30 minutes until foaming subsided. The resulting reaction solution was washed with 20 g of 1N aqueous hydrochloric acid. After repeating this operation three times, the organic layer was collected, concentrated, and dropped into 200 g of methanol to precipitate the polymer, and the solid was collected using a Buchner funnel. The polymer was dried under reduced pressure at 60°C to obtain 4.9 g of a white polymer represented by the following formula (A-6) (hereinafter also referred to as "polymer (A-7)" or "PS-ω-CH(CN)2"). This polymer (A-7) had Mw of 5,350, Mn of 5,140, ​​and Mw / Mn of 1.04.

[0115] [ka]

[0116] <Preparation of Composition> The solvents [B] used in the preparation of the compositions are shown below.

[0117] [[B] Solvent] B-1: Propylene glycol monomethyl ether acetate (PGMEA)

[0118] [Comparative Example 1] To 1.30 g of (A-1) as the component [A], 98.7 g of (B-1) as the solvent [B] was added, stirred, and then filtered through a high-density polyethylene filter having pores of 0.45 μm to prepare composition (S-1).

[0119] [Comparative Example 2 and Examples 1 to 4 and 16] Compositions (S-2) to (S-7) were prepared in the same manner as in Comparative Example 1 above, except that the types and amounts of each component shown in Table 1 below were used.

[0120] [Table 1]

[0121] <Membrane formation> [Comparative Example 3] An 8-inch copper substrate was cut to 3 cm x 3 cm, and the composition (S-1) prepared above was spin-coated at 1,500 rpm for 20 seconds using a spin coater ("MS-B300" from Mikasa Co., Ltd.), and then baked at 150°C for 180 seconds. Thereafter, unadsorbed film was removed using propylene glycol monomethyl ether acetate.

[0122] [Comparative Examples 4 to 8 and Examples 4 to 15, 17 to 19] A film was formed in the same manner as in Comparative Example 3, except that the substrate (copper substrate, cobalt substrate, tungsten substrate, or Si oxide substrate) and composition shown in Table 3 below were used.

[0123] <Evaluation of area selectivity of membrane formation> (Measurement of surface contact angle values) The contact angle value of the surface of the substrate on which the composition was applied and baked was measured using a contact angle meter ("Drop Master DM-501" manufactured by Kyowa Interface Science Co., Ltd.) The measured contact angle values ​​are also shown in Table 3 below.

[0124] (Measurement of average film thickness and polymer density) The average thickness (unit: nm) of the film formed above was measured using a spectroscopic ellipsometer (JAWOOLLAM's "M2000D"). Furthermore, the density of the polymer [A], σ (unit: chains / nm 2 ) was calculated. σ = d × L × NA × 10 -21 / Mn (In the above formula, d is the density of the polymer [A] (unit: g / cm 3 ) L is the average thickness of the film (unit: nm). NA is Avogadro's number. Mn is the number average molecular weight of the [A] polymer. The average thickness L of the film and the density σ of the polymer [A] are also shown in Table 3 below.

[0125] <Wet peelability evaluation of film> An 8-inch substrate (copper substrate, cobalt substrate, tungsten substrate or Si oxide substrate) was cut into 3 cm x 3 cm, and the composition shown in Table 3 below was spin-coated at 1,500 rpm for 20 seconds using a spin coater ("MS-B300" by Mikasa Co., Ltd.), and then baked at 150°C for 180 seconds. Then, propylene glycol monomethyl ether acetate was used to remove unadsorbed film. Next, the contact angle value of the surface was measured using the contact angle meter, and the substrate was immersed in a petri dish filled with acetic acid for 3 minutes, and then washed with a mixed solution of propylene glycol monomethyl ether acetate / ethyl lactate (8 / 2 (mass ratio)), and the contact angle value of the substrate surface was measured using the contact angle meter. The value of the decrease in the contact angle value is shown in Table 3 below. The decrease in the contact angle value confirmed the peeling of the film.

[0126] <Metal oxide blocking evaluation> In order to evaluate the state of film formation on the surface of each substrate on which the composition was applied and baked in the above <Film formation>, a metal oxide blocking evaluation was performed to measure the degree of inhibition of oxide layer formation by ALD.

[0127] [ALD Evaluation] Metal oxide blocking evaluation was performed using Cambridge Nanotech FIJI at Stanford University under the conditions shown in Table 2 below. Tetrakis(dimethylamino)hafnium was used as the precursor, and water was used as the co-catalyst. The ALD cycle was fixed at 47 cycles, and the presence or absence of oxide layer formation was confirmed for the substrate on which the composition was applied and baked.

[0128] [Table 2]

[0129] [XPS evaluation] The Hf content on the coating film after the ALD evaluation was quantified by ESCA analysis. ESCA was performed using ULVAC's "Quantum200" to quantify the Hf content, excluding the coating film and substrate components, under the condition of 100 μm diameter, using Hf4f, and then the percentage was calculated. At this time, the higher the "ALD tolerance" value, the higher the Hf blocking performance of the film.

[0130] [Table 3]

[0131] The results in Table 3 show that, according to the compositions of the examples, a film that can be wet-peeled in a selective area can be formed at a high density on the surface of a substrate containing metal atoms in its surface layer, and that this film can exhibit high blocking performance against the formation of metal oxides by the ALD method. [Industrial Applicability]

[0132] According to the composition and the method for producing a substrate of the present invention, a film capable of being wet-peeled in a selective area can be formed at a high density on the surface of a substrate containing metal atoms in the surface layer, and this film can exhibit high blocking performance against metal oxide formation by the ALD method or the CVD method. The polymer of the present invention can be suitably used as a polymer component of the composition. Therefore, the composition, the method for producing a substrate, and the polymer can be suitably used in the processing of semiconductor devices, which are expected to become increasingly finer in the future.

Claims

1. A group containing two or more cyano groups, -B(OR) 2 a group containing -PO(OR) 2 and groups containing -P(OR) 2 A polymer having at least one first group selected from the group consisting of groups including the following at an end of its main chain (wherein each R is independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms); Solvent and A composition comprising:

2. The composition described in claim 1, wherein the polymer has at least one structural unit selected from the group consisting of structural units derived from substituted or unsubstituted styrene, structural units derived from (meth)acrylic acid or a (meth)acrylic acid ester, structural units derived from substituted or unsubstituted ethylene, and structural units containing a crosslinkable group.

3. The composition of claim 1, wherein the polymer has structural units derived from substituted or unsubstituted styrene.

4. A step of directly or indirectly applying the composition according to any one of claims 1 to 3 to a substrate containing metal atoms in a surface layer; A step of heating the coating film formed by the coating step; A method for manufacturing a substrate comprising the steps of:

5. The method for manufacturing a substrate according to claim 4 , wherein the base material has a first region on a surface layer thereof that contains the metal atoms, and a second region on a surface layer thereof that does not contain the metal atoms.

6. 6. The method for producing a substrate according to claim 4, wherein the metal atoms constitute a simple metal, an alloy, a conductive nitride or a silicide.

7. 7. The method for producing a substrate according to claim 4, 5 or 6, wherein the metal atom is copper, iron, zinc, cobalt, aluminum, titanium, tin, tungsten, zirconium, tantalum, germanium, molybdenum, ruthenium, gold, silver, platinum, palladium or nickel.

8. After the heating step, a step of contacting the film formed by the heating step with a removal liquid The method for manufacturing a substrate according to claim 4 , further comprising:

9. The method for manufacturing a substrate according to claim 8, wherein the remover contains at least one selected from the group consisting of an acid and a base.

10. A group containing two or more cyano groups, -B(OR) 2 a group containing -PO(OR) 2 and groups containing -P(OR) 2 A polymer having at least one group selected from the group consisting of groups including the following at an end of the main chain (wherein R is each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms).

11. The polymer described in claim 10, having at least one structural unit selected from the group consisting of structural units derived from substituted or unsubstituted styrene, structural units derived from (meth)acrylic acid or a (meth)acrylic acid ester, structural units derived from substituted or unsubstituted ethylene, and structural units containing a crosslinkable group.

12. The polymer of claim 10 having structural units derived from substituted or unsubstituted styrene.

Citation Information

Patent Citations

  • Method for forming pattern in self assembled monolayer of organic molecule

    JP2003076036A

  • ORGANIC POLYMERS, ELECTRONIC DEVICES, AND METHODS

    JP2007538381A

  • Composition for nano-imprint, pattern forming method, etching resist and permanent film

    JP2009275195A

  • Resist material and pattern forming method using the same

    JP2014063045A

  • Photoresist composition, resist pattern formation method, polymer and compound

    JP2015096932A